2018
DOI: 10.1097/mat.0000000000000734
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Complication Rates Are Higher in Females after Continuous-Flow Left Ventricular Assist Device Implantation

Abstract: The aims of this analysis were to characterize the burden and timing of bleeding events in females versus males on left ventricular assist device (LVAD) support. A single-center retrospective review of 375 patients receiving continuous-flow LVADs was performed. Bleeding events included gastrointestinal, naso-oropharyngeal, gynecologic (GYN), intracranial hemorrhage (ICH), and mediastinal bleeding. Cox hazard ratios (HRs) [95% CI] and incident event rates for females versus males were calculated. Eighty-four fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Initiation of IV proton pump inhibitors is indicated, 19 especially when involvement of the gastric mucosa is suspected. Octreotide, a synthetic somatostatin analogue, has also been tried in gastrointestinal bleeding not responding to other measures 20 Other forms of bleeding that might be encountered in LVAD carriers include bleeding from the nasal or oral mucosa, seen usually as epistaxis, after teeth extraction, skin bruising, or haematuria 15 . Managing such bleeding episodes follows the principles applied to non‐LVAD supported patients and only if considered severe or long standing, referred to the relevant specialist.…”
Section: Bleedingmentioning
confidence: 99%
“…Initiation of IV proton pump inhibitors is indicated, 19 especially when involvement of the gastric mucosa is suspected. Octreotide, a synthetic somatostatin analogue, has also been tried in gastrointestinal bleeding not responding to other measures 20 Other forms of bleeding that might be encountered in LVAD carriers include bleeding from the nasal or oral mucosa, seen usually as epistaxis, after teeth extraction, skin bruising, or haematuria 15 . Managing such bleeding episodes follows the principles applied to non‐LVAD supported patients and only if considered severe or long standing, referred to the relevant specialist.…”
Section: Bleedingmentioning
confidence: 99%
“…Female sex has been a predisposing factor in other analysis. 8,28,66 Whereas GIB might facilitate a sooner transplantation in LVAD carriers, ICH more often renders the patient ineligible for transplant, depending on the residual morbidity. 52 There are several possible causes of haemorrhagic stroke in patients with LVAD, such as anticoagulation, haemorrhagic conversion after infarction, the acquired von Willebrand syndrome as a result of mechanical destruction, and proteolysis of high-molecular-weight multimers of von Willebrand factor 8 and rupture of histologically fragile vessels caused by the non-physiological continuous pulseless flow.…”
Section: Haemorrhagic Strokementioning
confidence: 99%
“…Some patient populations are at increased risk of bleeding. In the case of GIB, risk factors include older age, 28 lower body mass index, history of GIB prior to LVAD implant, smoking, elevated international normalized ratio (INR), and a low platelet count. 29 Patients with pre‐implant right ventricular failure have been prone to development of bleeding complications, possibly due to hepatic congestion and subsequent coagulopathy.…”
Section: Bleeding: Gastrointestinal and Non‐gastrointestinalmentioning
confidence: 99%
“…Despite the predominance of male patients with LVAD, ICH is more common among women. 14,16,18,[44][45][46][80][81][82][83][84] Analysis of the INTERMACS found female sex as an independent risk factor (hazard ration: 1.65), 14 and a recent systematic review showed that women have a 50% higher rate of ICH (12.32 vs. 6.13% for men). 83 The underlying mechanism for this sex effect is not known, although sexual hormones and smaller body surface areas may play a role.…”
Section: Sexmentioning
confidence: 99%